Temperature-gradient-induced massive augmentation of solute dispersion in viscoelastic micro-flows. (25th August 2020) - Mukherjee, Siddhartha; DasGupta, Sunando; Chakraborty, Suman
Abstract : Abstract : Enhancing solute dispersion in electrically actuated flows has always been a challenging proposition, as attributed to the inherent uniformity of the flow field in the absence of surface patterns. Over the years, researchers have focused their attention towards circumventing this limitation, by employing several fluidic and geometric modulations. However, the corresponding improvements in solute dispersion often turn out to be inconsequential. Here we reveal that by exploiting the interplay between an externally imposed temperature gradient, subsequent electrical charge redistribution and ionic motion, coupled with the rheological complexities of the fluid, one can achieve enhancement of up to one order of magnitude of solute dispersion in a pressure-driven flow of an electrolyte solution. Our results demonstrate that the complex coupling between thermal, electrical, hydrodynamic and rheological parameters over small scales, responsible for such exclusive phenomenon, can be utilized in designing novel thermally actuated microfluidic and bio-microfluidic devices with favourable solute separation and dispersion characteristics.